2014
DOI: 10.1088/1612-2011/11/6/065604
|View full text |Cite
|
Sign up to set email alerts
|

Label-free monitoring of colorectal adenoma–carcinoma sequence based on multiphoton microscopy

Abstract: The monitoring and evaluation of colorectal adenoma–carcinoma sequence during endoscopy are important for endoscopic resection of precursor lesions to disrupt the adenoma–carcinoma sequence and halt progression to invasive neoplastic disease. In this study, multiphoton microscopy (MPM) was used to identify different stages during the development of colorectal adenocarcinoma including adenoma with low-grade and high-grade dysplasia, and adenocarcinoma invading the submucosa. It was found that by combining two-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The nuclear area in tumor tissues is 44.06 ± 1.66 μm 2 (Table 1), which is far smaller than other kinds of cancerous cells [15], and the small standard deviation further demonstrates that the neuroendocrine cells are uniform in shape with round nuclei and minimal cellular pleomorphism.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The nuclear area in tumor tissues is 44.06 ± 1.66 μm 2 (Table 1), which is far smaller than other kinds of cancerous cells [15], and the small standard deviation further demonstrates that the neuroendocrine cells are uniform in shape with round nuclei and minimal cellular pleomorphism.…”
Section: Resultsmentioning
confidence: 91%
“…To be specific, the nuclear-to-cytoplasmic ratio in tumor tissues is 1.07 ± 0.27 instead of the normal 0.21 ± 0.02 (Table 1), indicating it may be used as a predictive factor for quantitatively monitoring the gastrointestinal tumor progression [15,19]. Figure 3 displays that submucosa is mainly made up of collagen fibers (blue arrow in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen content alteration in the normal and cancerous tissue from colorectal submucosa and muscularis propria layers MPM has several unique advantages of being label-free, intrinsic optical sectioning ability, near-infrared excitation for deep penetration depth into tissue, reduced photobleaching and phototoxicity in the out-of-focus regions, and the capability of providing quantitative information. It has been used to examine the potential applications in the field of colorectal cancer including monitoring colorectal cancer progression [24], [25], detecting tumor metastasis and microenvironment [26]- [28], evaluating colorectal cancer therapy response [29], and visualizing and ablating preinvasive colorectal cancer cells [30]. In this paper, this technique was extended to assess colorectal carcinoma invasion depth in the colorectal submucosa or muscularis propria layers.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that MPM can reveal the morphological changes of epithelial cells and glands at different stages during the development of colorectal adenocarcinoma including normal mucosa, low-grade dysplasia, high-grade dysplasia, and adenocarcinoma by combining 2PEF imaging and SHG imaging [9][10][11][12][13][14][15][16][17]. Representative images of colorectal cancer progression are demonstrated in figure 1.…”
Section: Monitoring Colorectal Cancer Progressionmentioning
confidence: 99%